Coordination under threshold uncertainty in a public goods game - Astrid Dannenberg; Andreas Löschel; Gabriele Paolacci; Christiane Reif; Alessandro Tavoni (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
We explored experimentally how threshold uncertainty affects coordination success in a threshold public goods game. Whereas all groups succeeded in providing the public good when the exact value of the threshold was known, uncertainty was generally detrimental for the public good provision. The negative effect of threshold uncertainty was particularly severe when it took the form of ambiguity, i.e. when players were not only unaware of the value of the threshold but also of its probability distribution. Early signaling of willingness to contribute and share the burden equitably helped groups in coping with threshold uncertainty.
Keywords: C72; C92; H41; Q54; 330; Public good; threshold uncertainty; ambiguity; experiment